Lights and Shadows of Media Literacy in the Spanish Education System: A way to reach the objectives proposed by Europe - Pérez-Femenía, Esther; Iglesias-García, Mar (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Internet use among teenagers is a majority practice across Europe and Spain is at the forefront, but only one in three Spanish young people aged 16-24 can identify the sources of what they read on social networks. Disinformation or fake news is on the rise. The objectives of this research focus on analysing whether Media and Information Literacy (MIL) training exists in the Spanish education system and whether it is adequate. It also presents how this subject has been introduced in some of the leading countries in the discipline, such as France, Great Britain and the USA.